OPTIMALISASI PENDIDIKAN KARAKTER MELALUI PENERAPAN ENVIRONMENT PROJECT-BASED LEARNING TERINTEGRASI MEDIA AUDIO VISUAL - Ichsan Fauzi Rachman; Fikri Hakim; Welly Nores Kartadireja; Agi Ahmad Ginanjar (Balai Besar Guru Penggerak Jawa Timur, 2023)
Environment project-based learning integrated audio-visual media is a learning method that involves students in projects related to the surrounding environment.The purpose of this study is to determine the effect ofenvironment project-based learning integrated audio-visual media on student discipline. This study uses a quantitative method with the type of experimental research using design preexperimental design, that isthe one group pretest posttest design. The population of this research was class VIIIA students of SMPIT Insan Kamil, which consisted of 20 students. The sampling technique used is saturated sampling. The data collection method was carried out using a non-test in the form of a questionnaire sheet. Hypothesis testing was carried out using a nonparametric test using the Wilcoxon formula. The results showed that there was an influence from the Environment project-based learning model that was integrated with audio-visual media on student discipline which could be seen from the posttest score which was higher than the pretest score for discipline. AbstrakEnvironment project-based learning terintegrasi media audio visual merupakan metode pembelajaran yang melibatkan siswa dalam proyek yang berhubungan dengan lingkungan sekitar. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari environment project-based learning terintegrasi media audio visual terhadap kedisiplinan siswa. Penelitian ini menggunakan metode kuantitatif dengan tipe penelitian eksperimen menggunakan desain preexperimental design, yaitu the one group pretest posttest design. Populasi penelitian ini adalah siswa kelas VIIIA SMPIT Insan Kamil yang berjumlah 20 siswa. Teknik sampling yang digunakan adalah sampling jenuh. Metode pengumpulan data dilakukan menggunakan nontes berupa lembar angket. Uji hipotesis dilakukan menggunakan uji nonparametrik dengan menggunakan formula Wilcoxon. Hasil penelitian menunjukkan adanya pengaruh dari model Environment project-based learning yang terintegrasi dengan media audio visual terhadap kedisiplinan siswa yang dapat dilihat dari nilai posttest yang lebih tinggi daripada nilai pretest sikap disiplin.